Role of ERBB3 in ERBB4-induced oncogenic cell transformation - Tuohisto-Kokko, Aura (My University, 2025)
ERBB3 and ERBB4 are part of the epidermal growth factor receptor family (EGFR/ERBB/HER) of receptor tyrosine kinases. Genetic alterations affecting ERBB receptors are known to cause multiple cancers, and while there are various ERBB-targeted therapy options available, resistance is inevitable. Function of ERBB4 has not been fully characterized in cancer due to its ambiguous role and complex regulation. In general, the oncogenic activity of ERBB4 has been connected to heterodimerization with EGFR or ERBB2. Interestingly, our study has identified an upregulation of ERBB3 in the oncogenic cell transformation mediated by an activating ERBB4 S303F mutation. The aim of this study was to investigate the role of ERRB3 in ERBB4-mediated oncogenic transformation by creating an Erbb3 knockdown model in ERBB4 expressing cells. Stable knockdown of ERBB3 was generated by lentiviral murine Erbb3 shRNA transduction of interleukin-3 (IL3)-dependent murine lymphoid Ba/F3 cells, which also stably expressed wild-type ERBB4 or ERBB4 S303F, or were transduced with an empty vector control. The oncogenic cell transformation potential was assessed by IL3-deprivation in the presence or absence of exogenous neuregulin-1 (NRG-1), a shared ligand of ERBB3 and ERBB4, and analyzed with MTT viability assay. Receptor expression and knockdown efficiency were confirmed with western blotting. The study showed that ERBB3 can participate in ERBB4-mediated cell transformation. Erbb3 knockdown significantly impaired the growth of NRG-1-independent cells upon IL3-deprivation and decreased the transforming potential of NRG-1-dependent cells. The results suggest that while ERBB3 may enhance the ERBB4-mediated transformation, ERBB3 might be less important in the presence of NRG-1 or in supporting cell growth after transformation. Further research in additional models on the co-operation of ERBB4 and ERBB3 in cancer is warranted to evaluate their potential as therapeutic targets.
Keywords: ERBB4, ERBB3, oncogene, shRNA, transformation